Materials selection in mechanical design - Ashby, Michael F., 1935- (Libros electrónicos en Ebscohost, 2010)
Understanding materials, their properties and behavior is fundamental to engineering design, and a key application of materials science. Written for all students of engineering, this book describes the procedures for material selection in mechanical design.